ASOSIASI SPESIES TUMBUHAN OBAT LANGKA DI BEBERAPA KAWASAN HUTAN TAMAN NASIONAL, PULAU JAWA - Hidayat, Syamsul (Perhimpunan Biologi Indonesia, 2012)
Association of endangered medicinal plants in some forest areas of national parks in Jawa. The existences of medicinal plants in the forest is decreasing and most of them are becoming scarce. Some species of endangered medicinal plants spread over the area national parks onthe island of Java. The inventory has been widely performed, but the studies of the existence of the species concerned associated with other species as well as with environmental factors are still very rare. This paper presents the results of association analysis interspecies with chisquare test and species-habitat associations using Canoco for windows 4.5. The results show that there is no interspecies association in general, but a positive association multispecies hasoccurred in the area of Meru Betiri NP and negative association multispecies occurred in Alas Purwo NP and Bromo Tengger Semeru NP. Ordination plot show that Eucresta horsfieldii has association with the altitude and has not associated with other rare medicinal plants. While Arcangelisia flava is not associated with environmental factors as well as other species of medicinal plants.Key words: endangered medicinal plants, association analysis